IMA Genome - F13 - P. Markus Wilken; Janneke Aylward; Ramesh Chand; Felix Grewe; Frances A. Lane; Shagun Sinha; Claudio Ametrano; Isabel Distefano; Pradeep K. Divakar; Tuan A. Duong; Sabine Huhndorf; Ravindra N. Kharwar; et al. (IMA Fungus)
ABSTRACT Draft genomes of the fungal species Ambrosiella cleistominuta, Cercospora brassicicola, C. citrullina, Physcia stellaris, and Teratosphaeria pseudoeucalypti are presented. Physcia stellaris is an important lichen forming fungus and Ambrosiella cleistominuta is an ambrosia beetle symbiont. Cercospora brassicicola and C. citrullina are agriculturally relevant plant pathogens that cause leaf-spots in brassicaceous vegetables and cucurbits respectively. Teratosphaeria pseudoeucalypti causes severe leaf blight and defoliation of Eucalyptus trees. These genomes provide a valuable resource for understanding the molecular processes in these economically important fungi.